Wartość diagnostyczna MSCT w chorobie niedokrwiennej serca u pacjentów z dodatnią próbą wysiłkową = Diagnostic value of MSCT in ischemic heart disease in patients with positive exercise test - Tomaszewski, Michał; Kozioł, Maciej; Kozioł, Jadwiga; Zadrąg-Olko, Agnieszka; Tomaszewski, Andrzej; Łuczyk, Robert (Journal of Education, Health and Sport, 2016)
Tomaszewski Michał, Kozioł Maciej, Kozioł Jadwiga, Zadrąg-Olko Agnieszka, Tomaszewski Andrzej, Łuczyk Robert. Wartość diagnostyczna MSCT w chorobie niedokrwiennej serca u pacjentów z dodatnią próbą wysiłkową = Diagnostic value of MSCT in ischemic heart disease in patients with positive exercise test. Journal of Education, Health and Sport. 2016;6(5):341-348. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53148 http://ojs.ukw.edu.pl/index.php/johs/article/view/3529 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. WARTOŚĆ DIAGNOSTYCZNA MSCT W CHOROBIE NIEDOKRWIENNEJ SERCA U PACJENTÓW Z DODATNIĄ PRÓBĄ WYSIŁKOWĄ Diagnostic value of MSCT in ischemic heart disease in patients with positive exercise test Michał Tomaszewski1, Maciej Kozioł2, Jadwiga Kozioł1, Agnieszka Zadrąg-Olko3, Andrzej Tomaszewski1, Robert Łuczyk4 1Klinika Kardiologii, Samodzielny Publiczny Szpital Kliniczny nr 4 w Lublinie 2Uniwersytet Medyczny w Lublinie 3Oddział Onkologii Klinicznej, Samodzielny Publiczny Szpital Wojewódzki im. Papieża Jana Pawła II, Zamość 4Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie Abstract Introduction: The ECG stress test remains the most popular non-invasive diagnostic tool in coronary vascular disease (CVD) diagnostics. However, it is characterized by low sensitivity (50%), thus, it was marginalized in the latest ESC guidelines for myocardial revascularization. The development of imaging techniques provided medicine with new methods of non-invasive diagnostics for coronary CVD. One of those techniques is multislice computed tomography (MSCT), which sufficient time and spatial resolution allows a reliable assessment of the coronary arteries. High negative predictive value of this method is particularly important, as it allows the waiver of further conservative treatment, tests and invasive procedures. Aim: The aim of the study was to determine the usefulness of MSCT in CVD diagnostics in patients with positive ECG stress test. Methods: The study was conducted on 100 consecutive patients (65% females, mean age 55 ± 8,9 years) with positive ECG stress test result. All of the patients underwent a CT scan of coronary arteries on 64 row CT. The retrospective analysis was based on the data obtained from the referrals issued by doctors of cardiology clinics. Analyzed parameters were: age, sex, BMI, the character of a referral (stable, urgent, sudden), blood pressure, heart rate and CCS class of a patient. Results: Most (84%) of the patients with positive result of ECG stress test, had no significant changes in their coronary arteries, only 16% had advanced changes. Statistically significant correlations between age, sex, indications for diagnostics and diagnosis were proven. Also, the correlation between Calcium Score and diagnosis was demonstrated. Conclusion: Conducting an MSCT imaging in patients with positive ECG stress test can lower the number of patients referred for an invasive treatment. Key words: CVD, coronary vascular disease, ECG stress test, MSCT. Abstrakt Wstęp: Elektrokardiograficzna próba wysiłkowa pozostaje najpopularniejszym nieinwazyjnym narzędziem w diagnostyce choroby niedokrwiennej serca. Ze względu na swoją niską czułość została ona zmarginalizowana w najnowszych wytycznych ESC dotyczących rewaskularyzacji mięśnia sercowego. Rozwój technik obrazowania dostarczył jednak nowych metod obrazowania naczyń wieńcowych. Jedną z tych metod jest wielorzędowa tomografia komputerowa (MSCT), charakteryzująca się wystarczającą rozdzielczością czasową i przestrzenną, by możliwa była wiarygodna ocena naczyń wieńcowych. Szczególnie ważna jest wysoka ujemna wartość predykcyjna tej metody, która pozwala na uniknięcie niepotrzebnych dalszych badań czy inwazyjnych zabiegów. Cel badania: Celem badania było ustalenie wartości MSCT w diagnostyce choroby niedokrwiennej serca u pacjentów z dodatnią próbą wysiłkową. Materiały i metody: Badanie przeprowadzono wśród 100 kolejnych pacjentów (65% kobiet, średni wiek 55± 8,9 lat) z dodatnim wynikiem elektrokardiograficznej próby wysiłkowej. U wszystkich pacjentów wykonano obrazowanie tętnic wieńcowych za pomocą 64-rzędowego tomografu komputerowego. Retrospektywna analiza opisowa grupy została oparta na informacjach uzyskanych ze skierowań wystawionych przez lekarzy z poradni kardiologicznych na badanie MSCT. Analizowanymi parametrami były: wiek, płeć, BMI, tryb skierowania na badanie (przypadek stabilny, pilny, nagły), ciśnienie krwi, częstość akcji serca oraz klasa CCS do której zakwalifikowano pacjenta. Wyniki: U większości (84%) pacjentów z dodatnim wynikiem próby wysiłkowej badanie MSCT nie wykazało istotnych zmian w tętnicach wieńcowych, tylko u 16% pacjentów stwierdzono zaawansowane zmiany. Udowodniono istotne statystycznie korelacje między wiekiem, płcią i wskazaniem do wykonania badania a ostateczną diagnozą. Wykazano także korelację między wynikiem Calcium Score a diagnozą. Wnioski: Wykonanie badania MSCT u pacjenta z dodatnim wynikiem elektrokardiograficznej próby wysiłkowej może obniżyć liczbę pacjentów kierowanych do leczenia inwazyjnego. Słowa kluczowe: choroba wieńcowa, choroba niedokrwienna serca, elektrokardiograficzna próba wysiłkowa, MSCT.